Atomic-scale analysis of early-stage precipitation in Ti(Al, Si)3 alloy. (15th November 2017) - Zhang, Tongtong; Fan, Guohua; Wu, Hao; Cui, Xiping; Huang, Meng; Miao, Kesong; Geng, Lin
Abstract: The early-stage precipitation behavior of Si in Ti(Al, Si)3 alloy heated to 800 °C and then down to room temperature (RT) is characterized at the atomic scale by in-situ transmission electron microscope (TEM). Three types of nanoparticles were observed in Ti(Al, Si)3 alloy during the early-stage precipitation, which contain Si-rich nanoclusters, Ti7 Al5 Si12 precipitates as well as Ti5 Si3 precipitates. The precipitation sequence and orientation relationship (OR) for the early-stage precipitation in Ti(Al, Si)3 alloy are as follows: (i) small Si-rich nanoclusters firstly form in TiAl3 matrix due to the segregation of Si, coexisting with larger Si-rich nanoclusters; (ii) Si-rich nanoclusters that reach the critical size (20–30 nm) serve as nucleation sites for metastable Ti7 Al5 Si12 precipitates with an OR: 002 TiAl 3 / / 1 1 ¯ 6 Ti 7 Al 5 Si 12, 1 ¯ 10 TiAl 3 / / 115 1 ¯ Ti 7 Al 5 Si 12 ; and then (iii) the formation of Ti5 Si3 precipitates is by transformation of metastable Ti7 Al5 Si12 with an OR: 10 1 ¯ 0 Ti 5 Si 3 / / 001 Ti 7 Al 5 Si 12, 1 2 ¯ 13 Ti 5 Si 3 / / 010 Ti 7 Al 5 Si 12 . Graphical abstract: Highlights: The early-stage precipitation behavior in Ti(Al, Si)3 alloy subjected to in situ heating and cooling was investigated. The early-stage precipitation were formed in the following order: Si-rich nanoclusters, Ti7 Al5 Si12 and Ti5 Si3 . The Si-rich nanoclusters, Ti7 Al5 Si12 and Ti5 Si3 could coexist in Ti(Al, Si)3 alloy during the early-stage precipitation.